Accountability for Village Fund Allocation Management in Punagaya Village, Bangkala District, Jeneponto Regency - Andi Risma Jaya; Muslimin Muslimin (xxxx-xxxx, 2023)
Accountability can be interpreted as the obligations of individuals or authorities who are entrusted with managing public resources and those concerned with them to be able to answer matters concerning their accountability. Based on this, the study aims to describe and explain the accountability of village fund allocation management in Punagaya Village, Bangkala District, Jeneponto Regency. This type of research is descriptive quantitative and the sample members are 40 employees and the community using a probling sampling technique that uses all members of the population. Data was collected using instruments in the form of; Observation, Questionnaire and Documentation of respondents. The data were analyzed quantitatively descriptive statistics using a simple frequency table. The results of the study indicate that there is accountability in the management of village fund allocations in Punagaya Village, Bangkala District, Jeneponto Regency. Factors constraining accountability for the allocation of village funds are skills/abilities, desires and level of participation. Keywords: Accountability, Allocationof Village Fund